Damper connector - Hejazi, Farzad; Jaafar, Mohd Saleh; Mohd Zain, Mohd Azmi; Vaghei, Ramin; Ebrahimi, Esmaeil (2014)
The present invention discloses a damper connector (100) that connects structural elements (10a, 10b) in order to increase the overall damping so as to improve their performance by dissipating part of the energy transferred to them from dynamic load due to earthquakes, wind or any source of vibrations. The damper connector (100) comprises an upper housing member (102) and a lower housing member (106) in communication with each other, each of the housing members (102, 106) having a base plate (108, 120) with parallel plates (110, 122) that are perpendicular to the base plate (108,120), both the upper housing member (102) and the lower housing member (106) are in communication with each other such that, the parallel plates (110) of the upper housing member (102) alternate with the parallel plates (122) of the lower housing member (106); and the parallel plates (110, 122) are spaced apart forming parallel slots for insertion of a damping member (104).